2002
DOI: 10.1097/00007632-200204010-00017
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and Complications of Long Fusions to the Sacrum in Adult Spine Deformity

Abstract: Attention to sagittal balance is critical in these patients. Revision surgery is as safe and effective as primary surgery. According to the current findings, the Luque-Galveston fixation technique has an unacceptably high rate of pseudarthrosis, and this method is not recommended for adult deformities. Currently, the authors are using bicortical and triangulated sacral screws with an anterior interbody support in patients with good bone stock, but only when the spine balance is restored. Otherwise, they recomm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
104
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 370 publications
(107 citation statements)
references
References 20 publications
2
104
0
1
Order By: Relevance
“…The average number of levels fused was 6.08 segments (range [4][5][6][7][8] in the L5 group and 6.09 (range 4-9) in the sacrum group with no statistical difference. The upper instrumented vertebra (UIV) was T9 in 2 patients, T10 in 11 patients, T11 in 3 patients, T12 in 3 patients, and L1 in 5 patients in the L5 group.…”
Section: Operative Proceduresmentioning
confidence: 83%
See 3 more Smart Citations
“…The average number of levels fused was 6.08 segments (range [4][5][6][7][8] in the L5 group and 6.09 (range 4-9) in the sacrum group with no statistical difference. The upper instrumented vertebra (UIV) was T9 in 2 patients, T10 in 11 patients, T11 in 3 patients, T12 in 3 patients, and L1 in 5 patients in the L5 group.…”
Section: Operative Proceduresmentioning
confidence: 83%
“…Higher rates of pseudarthrosis may be associated with a less rigid fixation method. Emami et al [6] found a significant pseudarthrosis rate in 36% of patients with the Luque Galveston technique and 14% of patients with the sacral and iliac screws. Bridwell et al [2] noted that they did not have a failure of the sacral screws by combination with anterior structural support and iliac screw fixation.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Poor bone stock or osteopenia, older fixation systems and inadequate fixation, failure to achieve spinal coronal and sagittal balance, and patient-specific factors have all been implicated in contributing to poor outcomes. [1][2][3][4][5][6] Emami et al 7 have addressed 3 concepts that derived from previous work and their own observations: (1) the benefit of interbody structural support at the lumbosacral junction, (2) the emphasis of L5 and S1 pedicle fixation, and (3) the importance of achieving spinal balance. In their 2002 retrospective study of 54 patients, they reported an 8.5% pseudarthrosis rate in 12 patients treated with posterior Isola segmental instrumentation using triangulated bicortical sacral screws and no iliac fixation.…”
mentioning
confidence: 99%